A database of expressed genes From Cochliomyia hominivorax (Diptera: Calliphoridae) - Guerrero, F.D.; Dowd, S.E.; Djikeng, Appolinaire; Wiley, G.; MacMillan, Susan; Saldivar, L.; Najar, F.; Roe, B.A. (Oxford University Press, 2009)
We used an expressed sequence tag and 454 pyrosequencing approach to initiate a study of the genome of the screwworm, Cochliomyia hominivorax (Coquerel) (Diptera: Calliphoridae). Two normalized cDNA libraries were constructed from RNA isolated from embryos and second instar larvae from the Panama 95 strain. Approximately 5,400 clones from each library were sequenced from both the 5? and 3? directions using the Sanger method. In addition, double-stranded cDNA was prepared from random-primed polyA RNA purified from embryos, second-instar larvae, adult males, and adult females. These four cDNA samples were used for 454 pyrosequencing that produced ?300,000 independent sequences. Sequences were assembled into a database of assembled contigs and singletons and used to search public protein databases and annotate the sequences. The full database consists of 6,076 contigs and 58,221 singletons assembled from both the traditional expressed sequence tag (EST) and 454 sequences. Annotation of the data led to the identification of several gene coding regions with possible roles in sex determination in the screwworm. This database will facilitate the design of microarray and other experiments to study screwworm gene expression on a larger scale than previously possible.